2018
DOI: 10.4025/actasciagron.v40i1.36372
|View full text |Cite
|
Sign up to set email alerts
|

<b>Di-nitrogen fixation at the early and late growth stages of soybean

Abstract: Soybean derives a significant portion of the required nitrogen (N) from the symbiosis with rhizobia bacteria. However, information on the available genetic variation for N 2 fixation capacity in different growth stages of soybean is limited. The objective of this study was to investigate the N 2 fixation capacity of 22 soybean lines compared with that of non-nodulating and supernodulating checks at the early and late growth stages and identify the most informative traits for selection. Two cycles of greenhouse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…Although nodule size has been suggested to influence BNF more than other nodule traits (de Araujo et al, 2017; Tajima et al, 2007; Voisin, Salon, Jeudy, & Warembourg, 2003b), contrarily greater fixation was seen in DM50I17 with smaller nodules than DM40R16. We confirm a genotypic effect on the timing of BNF (Hamawaki & Kantartzi, 2018) and additionally show this occurs for nodulation; however, nodulation and the timing of BNF were not correlated (Tables 3 and 4). Low RZT delays BNF and nodule formation (Zhang et al, 1995) in both genotypes (Tables 3 and 4) and therefore does not explain differences in N supply across sowing dates.…”
Section: Discussionsupporting
confidence: 80%
“…Although nodule size has been suggested to influence BNF more than other nodule traits (de Araujo et al, 2017; Tajima et al, 2007; Voisin, Salon, Jeudy, & Warembourg, 2003b), contrarily greater fixation was seen in DM50I17 with smaller nodules than DM40R16. We confirm a genotypic effect on the timing of BNF (Hamawaki & Kantartzi, 2018) and additionally show this occurs for nodulation; however, nodulation and the timing of BNF were not correlated (Tables 3 and 4). Low RZT delays BNF and nodule formation (Zhang et al, 1995) in both genotypes (Tables 3 and 4) and therefore does not explain differences in N supply across sowing dates.…”
Section: Discussionsupporting
confidence: 80%
“…Indeed, UFPI59 contributed for increasing the N content in lima bean and it can be correlated to the higher nodule size found with this strain. There is a strong correlation between nodule size and N accumulation in plants (Deliae et al, 2010;Voisin et al, 2015;Hamawaki & Kantartzi, 2018) and it corroborates with the results observed in this study. It can indicate that UFPI59 presents high effectiveness in contributing with N to lima bean.…”
Section: Resultssupporting
confidence: 92%
“…Doubled plant population of mungbean and lower intra-row spacing between sweet sorghum and mungbean have aggravated the competitive ability between sweet sorghum and mungbeanand thus led to a reduction of growth and yield parameters. Sweet sorghum would have been non-competitive and cooperative with soybean as it hasa greater ability to fix atmospheric nitrogen (range of 56-89 % of total plant N) compared to mungbean (45-76% of total plant N) and being able to make available a part of such N to associated plants [42]. The LAI, plant height and grain yield of intercropped sweet sorghum were significantly decreased by 10.5, 8.4, and 8.5 %, respectively, when N dose was reduced to 30 kg ha -1 compared to 60 kg ha -1 .…”
Section: Discussionmentioning
confidence: 99%